Antimony glasses with large nonlinear refractive indices, small two-photon absorption coefficients and ultrafast response at telecom wavelengths - De Araújo, C. B.; Gómez, L. A.; Falcão Filho, E. L.; Messias, D. N.; Misoguti, L.; Zílio, S. C.; Nalin, Marcelo [UNESP]; Messaddeq, Younes [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2007)
Nonlinear (NL) optical properties of antimony oxide based glasses (AG) were characterized for excitation wavelengths from 800 to 1600 m. The NL refractive indices, n2, and the two-photon absorption (TPA) coefficient, β, have been evaluated using the Z-scan technique. Values of n2≈ 10-15 - 10-14 cm2/W of electronic origin were measured and negligible TPA coefficients (β < 0.003 cm/GW) were determined. The response time of the nonlinearity is faster than 100 fs as determined using the Kerr shutter technique. The figure-of-merit usually considered for all-optical switching, T = 2βλ/n2 , indicates that AG are very good materials for ultrafast switches at telecom wavelengths. © 2007 IEEE.
Keywords: All-optical switching; Antimony oxide glasses; Nonlinear refractive index; Telecom wavelengths; Absorption; Antimony; Fiber optic networks; Glass; Light absorption; Light measurement; Light refraction; Luminescence of organic solids; Multiphoton processes; Optical data processing; Optical materials; Optical properties; Organic polymers; Photons; Refractive index; Refractometers; Telecommunication; Telecommunication systems; Antimony glasses; Electronic origins; Excitation wavelengths; Kerr shutters; Non linearities; Response times; Scan techniques; Two-Photon absorptions; Ultra fasts; Ultrafast switches; Optical switches